Evaluating deceased organ donation: a programme theory approach. Issue 3 (10th June 2014) - Manzano, Ana; Pawson, Ray
Abstract : Purpose: – Organ donation and transplantation services represent a microcosm of modern healthcare organisations. They are complex adaptive systems. They face perpetual problems of matching supply and demand. They operate under fierce time and resource constraints. And yet they have received relatively little attention from a systems perspective. The purpose of this paper is to consider some of the fundamental issues in evaluating, improving and policy reform in such complex systems. Design/methodology/approach: – The paper advocates an approach based on programme theory evaluation. Findings: – The paper explains how the death to donation to transplantation process depends on the accumulation of series of embedded, institutional sub-processes. Evaluators need to be concerned with this whole system rather than with its discrete parts or sectors. Policy makers may expect disappointment if they seek to improve donation rates by applying nudges or administrative reforms at a single point in the implementation chain. Originality/value: – These services represent concentrated, perfect storms of complexity and the paper offers guidance to practitioners with bio-medical backgrounds on how such services might be evaluated and improved. For the methodological audience the paper caters for the burgeoning interest in programme theory evaluation while illustrating the design phase of this research strategy.